2004
DOI: 10.1093/pcp/pci009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Full-length Enriched Expressed Sequence Tags of Stress-treated Poplar Leaves

Abstract: Poplar, whose genome is the first to be sequenced among woody plants, is a favorable model for plant biologists to enable them to understand molecular processes of growth, development and responses to environmental stimuli in trees. The sequence will allow the development of a strategy for improving environmental stress tolerance in forest trees. In this study, we have generated a full-length enriched cDNA library from leaves of axenically grown poplar (Populus nigra var. italica) subjected to environmental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…21,22) In tea leaves (C. sinensis), Chen et al 23) performed EST analysis of spring tender shoots. Park et al 24) also reported EST analysis of a subtractive cDNA library between young leaves and mature leaves, and identified several genes involved in catechin biosynthesis.…”
mentioning
confidence: 99%
“…21,22) In tea leaves (C. sinensis), Chen et al 23) performed EST analysis of spring tender shoots. Park et al 24) also reported EST analysis of a subtractive cDNA library between young leaves and mature leaves, and identified several genes involved in catechin biosynthesis.…”
mentioning
confidence: 99%
“…Although it was perhaps not surprising that these candidates were the highly abundant photosynthetic and housekeeping genes or enzymes of primary metabolism, it was not intuitive that such gene would be stably expressed under field conditions. The most abundant ESTs in the late-season cotton leaf library listed in Table 1 are similar to the list of the 20 most abundant ESTs noted by Nanjo et al (2004) in stresstreated poplar leaves (dehydration, chilling, salt, heat, ABA and peroxide-treated leaves) probably reflecting the naturally-stressed environment of field-grown irrigated cotton plants that are subject to daily heat and water stresses and natural infestations by pests and diseases.…”
Section: Discussionmentioning
confidence: 53%
“…Populus sp. has an average genome size of 550 Mbp and is estimated to contain about 58,000 genes, over twice as many as the Arabidopsis genome, which further supports the likelihood to find homologs of Arabidopsis genes in Populus (Nanjo et al, 2004;Wullschlege, Jansson, and Taylor, 2002). Finally, genomic DNA is highly conserved among the Populus genus (Sterky et al, 2004), which allows P. trichocarpa database to be applicable to various Populus species.…”
Section: Discussionmentioning
confidence: 68%
“…Another central assumption is that similar genes are at work and induced by RDX in the laboratory model A. thaliana and in Populus sp., which constitutes a model of forest trees and a model for phytoremediation studies. Sterky et al (2004) showed a considerable similarity between Arabidopsis and Populus genomes, which has already allowed the transfer of functional information from Arabidopsis to Populus (Nanjo et al, 2004). Nearly all gene families found in one species have homologs in the other.…”
Section: Discussionmentioning
confidence: 95%